2010
DOI: 10.1111/j.1478-3231.2010.02207.x
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding and managing lamivudine resistance in chronic hepatitis B: current approaches and potential strategies including pegylated interferon

Abstract: Since its approval for the treatment of chronic hepatitis B in 1998, lamivudine (LAM) has been used extensively throughout the world, because of its relatively low costs and favourable tolerability. However, clinical trials and cohort studies have demonstrated that a high rate of resistance to this drug develops and, as a result, it is no longer included as a first-line therapy in most current treatment guidelines. Nevertheless, because of its low cost, this drug continues to be used in many countries and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 104 publications
(150 reference statements)
0
12
0
Order By: Relevance
“…One of the core concepts is that active virus replication is required to develop resistant strains 14,18. Primary non-response to treatment, defined as a <1 log 10 drop in HBV DNA at week 12, as well as partial response (still detectable HBV DNA levels after 24 weeks of treatment) are both risk factors in developing anti-HBV resistance 14.…”
Section: Risk Factors For Lam Anti-hbv Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…One of the core concepts is that active virus replication is required to develop resistant strains 14,18. Primary non-response to treatment, defined as a <1 log 10 drop in HBV DNA at week 12, as well as partial response (still detectable HBV DNA levels after 24 weeks of treatment) are both risk factors in developing anti-HBV resistance 14.…”
Section: Risk Factors For Lam Anti-hbv Resistancementioning
confidence: 99%
“…Testing for resistance at baseline can help predict response to LAM, and therefore determine who is most appropriate for treatment 18. This may be especially useful in those with a prior treatment history, as their likelihood of LAM resistance is significantly higher.…”
Section: Reducing Risk Of Lam Anti-hbv Resistancementioning
confidence: 99%
“…Fifth, the current analysis did not include interferon-based strategies for dealing with LAM resistance. Some studies have suggested that a significant proportion of patients with LAM resistance who switched to pegIFNa-2a from LAM had a similar response to pegIFNa-2a as treatment-naïve patients [6]. Sixth, the utility scores for patients with LAM-resistant and multi-resistant CHB were assumed to be equal to those for naïve CHB.…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple rescue strategies for LAM-resistant CHB have been evaluated in clinical trials, the most commonly recommended strategies are ADV monotherapy (10 mg/day), combination therapy using LAM (100 mg/day) and ADV (10 mg/day), ETV monotherapy (1 mg/day) and TDF monotherapy (300 mg/day) [6]. Therefore, these 4 rescue strategies were included to compare their cost and effectiveness over time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation